2012
DOI: 10.1073/pnas.1115828109
|View full text |Cite
|
Sign up to set email alerts
|

Early ontogenic origin of the hematopoietic stem cell lineage

Abstract: Several lines of evidence suggest that the adult hematopoietic system has multiple developmental origins, but the ontogenic relationship between nascent hematopoietic populations under this scheme is poorly understood. In an alternative theory, the earliest definitive blood precursors arise from a single anatomical location, which constitutes the cellular source for subsequent hematopoietic populations. To deconvolute hematopoietic ontogeny, we designed an embryo-rescue system in which the key hematopoietic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 29 publications
5
51
0
Order By: Relevance
“…This finding is in line with data from timed rescue of Runx1 null mouse embryos, which showed that definitive, adult-type HSCs originate in the nascent extraembryonic mesoderm before the fetal liver initiates definitive hematopoiesis (Tanaka et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…This finding is in line with data from timed rescue of Runx1 null mouse embryos, which showed that definitive, adult-type HSCs originate in the nascent extraembryonic mesoderm before the fetal liver initiates definitive hematopoiesis (Tanaka et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…Tanaka et al (Tanaka et al, 2012) previously showed that restoration of Runx1 expression from the endogenous Runx1 locus at E6.5 and E7.5 could rescue EMP formation and viability of Runx1-deficient embryos, whereas restoring Runx1 expression at E8.0 or later could not. Their experimental design utilized Cre ERT expressed from one endogenous Runx1 allele to permanently restore Runx1 expression from the other, conditionally activated Runx1 allele.…”
Section: Discussionmentioning
confidence: 99%
“…The end of the requirement is likely to reflect the termination of a three-day process of EMP formation from endothelium. Tanaka et al also defined the beginning of the Runx1 requirement for HSC formation as E7.5 (Tanaka et al, 2012). Although they showed by transplantation experiments that HSCs were rescued when Runx1 was reactivated at E7.5, they did not directly assess HSC function by transplantation upon reactivation at later time points, and instead used fetal viability and CFU-C activity in the AGM region as surrogates for HSC rescue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation implied that some of the endothelial cells in these HSC-producing regions were derived from E7.5-labeled yolk sac cells. In a subsequent study, Tanaka et al developed an inducible Runx1 rescue system by a single tamoxifen injection in Runx1 knockout embryos [132]. Definitive hematopoiesis and HSC generation were rescued by a single injection of tamoxifen at E6.5 to E7.5, but not at any other time point [132].…”
Section: Seeking the Hsc Origin: Potential Yolk Sac Contribution To Hmentioning
confidence: 99%